Analysis of the expansion of medical staff in the care of ophthalmological emergencies in a university hospital: impacts on the university, professionalization, and for society - Amaral Navas, Morgana Helena; Mageste Rosa, Maria Luiza; Marchesi Mello, Luiz Guilherme; Cabral Silva, Thiago George; Silvares dos Santos, Lucyara; Gama Puppim, Nathalia; Grativol Costa Saraiva, Patrícia; Petersen Saraiva, Fábio (Guará Journal, 2025)
Since 2015, the Cassiano Antônio de Moraes University Hospital (HUCAM/UFES) has provided emergency ophthalmological care to the population through an extension project, establishing itself as a reference service, particularly for patients affected by corneal diseases. In October 2021, the clinical staff responsible for these services was expanded through a public recruitment process promoted by the Brazilian Hospital Services Company (EBSERH/Federal Government). The objective of this study was to analyze the impact of this expansion on both the service and the patients assisted. Data from each consultation were tabulated and analyzed, comparing equivalent periods: from October 1, 2021 to May 1, 2022 (period A) and from October 1, 2022 to May 1, 2023 (period B). An increase in the number of consultations and in the diversity of diagnoses was observed, without any negative impact on the care provided to patients with corneal diseases. It is concluded that the expansion of the clinical staff proved to be highly valuable for all parties involved, contributing to the improvement of academic and medical training, enhancing the quality of services provided by HUCAM/UFES, and delivering more efficient, qualified, and effective care to the population.
Keywords: Emergencies; Ophthalmological Services; Ophthalmology; University Health Service